Cinderella's Christmas secret - Kendrick, Sharon (Harlequin presents, 2020)
Cinderella's story will change forever ... with her festive secret! Hollie Walker knew Spanish businessman Maximo Diaz was off-the-charts gorgeous - and off-limits to a shy waitress. But with all his attention focused on her at her work Christmas party, Hollie couldn't deny herself the night of inescapable pleasure that followed ... Lone-wolf Maximo knew their encounter would be unforgettable - and unrepeatable. Yet now Hollie's at his castle ... to reveal she's pregnant. And a snowbound Christmas will force them to confront the dangerous passion they can no longer escape!